Pengaruh Penggunaan Tapping Box dan Kesadaran Wajib Pajak Terhadap Kepatuhan dengan Pemahaman Penggunaan Sistem Online Sebagai Variabel Pemoderasi (Studi Pada Wajib Pajak Hotel Yang Terdaftar di BPKAD Kabupaten Karangasem) - I Putu Arya Dirghayusa; I Nyoman Putra Yasa (JIMAT (Jurnal Ilmiah Mahasiswa Akuntansi) Undiksha, 2020)
This study aims to determine the use of tapping boxes and taxpayer awareness of compliance with understanding the use of online systems as moderating variables. This research is a type of quantitative research with a descriptive approach. The population and sample in this study are hotel taxpayers registered in BPKAD Karangasem Regency. The method of determining the sample used is simple random sampling technique, with a total sample of 221. Data used in this study are primary data collected through questionnaires to HRD Hotel Managers in Karangasem Regency. Furthermore, the data collected was tested by multiple linear regression analysis, T test, and interaction test (MRA). The results showed that the variable use of tapping boxes partially had a significant positive effect on hotel taxpayer compliance, the variable of taxpayer awareness did not have a significant positive effect on taxpayer compliance, and the understanding of the use of an online system weakened the relationship between the use of tapping boxes and taxpayer awareness of compulsory compliance hotel tax